2018
DOI: 10.1042/bsr20180011
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt antagonist and secreted frizzled-related protein 5: implications on lipid metabolism, inflammation, and type 2 diabetes mellitus

Abstract: Various reports have suggested that secreted frizzled-related protein (SFRP) 5 (SFRP5) plays a regulatory role in the processes of cellular proliferation and differentiation, by means of inactivating the Wnt/β-catenin signaling pathway. Recently, SFRP5 has been identified as an anti-inflammatory adipokine, which may be induced during preadipocyte proliferation, differentiation, and maturation. This review aims to identify the recent progress in the research and development of SFRP5 that can play a role in infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 67 publications
3
40
0
Order By: Relevance
“…Previous studies confirmed that vascular insulin resistance in the arterioles of visceral adipose tissue in obese subjects is associated with upregulated Wnt5a-JNK signalling [14]. Secreted frizzled-related protein 5 (Sfrp5) has been shown to antagonize the Wnt/β-catenin signalling pathway, reducing β-cell insulin secretion by inhibiting the noncanonical Wnt signalling pathway [15].…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies confirmed that vascular insulin resistance in the arterioles of visceral adipose tissue in obese subjects is associated with upregulated Wnt5a-JNK signalling [14]. Secreted frizzled-related protein 5 (Sfrp5) has been shown to antagonize the Wnt/β-catenin signalling pathway, reducing β-cell insulin secretion by inhibiting the noncanonical Wnt signalling pathway [15].…”
Section: Introductionmentioning
confidence: 89%
“…Currently, many studies provided the potential inhibitors of the Wnt signaling pathway. The major inhibitors for the Wnt signal pathway include Dickkopf-1 (DKK-1) ( 30 , 31 ), Frizzled-related protein (sFRP) ( 32 34 ), Wnt inhibitory factor-1 (WIF-1) ( 31 , 35 , 36 ), Ceberus (CER) ( 31 ), and salinomycin ( 37 ). These potential inhibitors for targeting the TDRKH-AS1 is worth to be constructed and evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes that are key regulators of lipid metabolism such as SCD, ACACA, FABP4, SFRP1, THRSP or the hub genes SFRP5 and FASN (Additional file 9: Table S9), also clustered in a tight co-expression module and they were significantly associated with linoleic and arachidonic fatty acids content in the gluteus medius muscle (Additional file 14: Table S14). The SFRP5 protein has been thoroughly studied as a central regulator of lipid accumulation and adipocytes differentiation, which are a result of an increased mitochondrial respiration promoted by SFRP5 blocking of Wnt signaling, hence repressing Wnt-induced oxidative metabolism [102]. The other identified SFRP element (SFRP1) has also been reported to be located in a genomic region overlapping a QTL for meat marbling [103,104].…”
Section: Weighted Co-expression Analyses Revealed Hub Genes Related Wmentioning
confidence: 99%